Peningkatan Hasil Belajar Dan Gotong Royong Pembelajaran Pak Dengan Model Pbl Berbantuan LKPD Di Kelas 2 Fase A SDN 03 Nanga Kalan - Agustinus Suharmanto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The implementation of the Merdeka curriculum at SDN 03 Nanga Kalan experiences obstacles, especially in the geographical aspect, with access that is difficult to reach, which affects the attitude of students who are tired due to the long journey. This affects the dynamics of learning Catholic religious education in phase A in class 2. Overcoming this, a classroom action research was carried out which was oriented towards a sense of mutual strengthening contained in the Pancasila student profile, namely the mutual cooperation dimension. The purpose of this study was to determine the increase in the dimension of mutual cooperation and learning outcomes in learning Catholic Religious Education through the Problem Based Learning learning model assisted by LKPD. Data collection techniques using observation, written tests, interviews and documentation conducted on 12 children. In cycle 1, the results of observing the dimensions of mutual cooperation based on the average achievement of the instrument obtained an average of 64% and learning outcomes reached 45% reaching KKTP, In cycle 2, the data obtained on the dimensions of mutual cooperation reached 87%, while for learning outcomes 100% of students reached KKTP. The conclusion obtained is that there is an increase in the dimension of mutual cooperation by 23% and an increase in learning outcomes by 65% from cycle 1 to cycle 2. This proves that the application of Problem Based Learning assisted by LKPD is effective for increasing the dimensions of mutual cooperation and student learning outcomes.